The role of social listening in promoting 100% smoke-free law in Shanghai - Sisi Wen; Wenwen Zhao (Tobacco Induced Diseases, 2018)
Background and challenges to implementation The Shanghai Regulation on Smoking Control in Public Places was enacted in 2009, but DSRs were allowed in some indoor places, making the protection for Shanghai's 24 million residents in Shanghai ineffective. Opportunities to amend the law arose in 2016, however, there was no consensus among policymakers in terms of DSRs. Public awareness about the ineffectiveness of DSRs in preventing secondhand smoke exposure was low, and the public was generally indifferent about this issue.